Sebuah COST EFFECTIVENESS ANALYSIS - Adiyatma, Krisna Hario; Mahmud; SUDADI; Calcarina Fitriani Retno Wisudarti; Djayanti Sari; Diah Ayu Puspandari (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2024)
Background : One of the frequent post-operative complications is pain, which is experienced by more than 80% of patients and 75% of them experience post-operative pain of moderate to severe intensity. Major abdominal surgery is a surgical procedure with moderate to severe postoperative pain intensity. Analgesic approach strategies that are often used are intravenous opioids and epidural analgesia. Epidural analgesia is considered the analgesic therapy of choice for post-major abdominal surgery, but at a higher cost when compared with intravenous opioids. The differences in route of administration, efficacy and side effect profiles make it important to assess the cost effectiveness between the two approaches as part of hospital quality control and cost management.Objective : To determine the cost effectiveness of epidural analgesia compared with intravenous opioids as analgetic after major abdominal surgery.Method : This study used a descriptive analytical design with decision tree analysis to assess clinical outcomes and estimated costs for two alternative therapies. Research samples were taken retrospectively from September – December 2022 at RSUP Dr. Sardjito Yogyakarta, using simple random sampling. The Incremental Cost Effectiveness Ratio (ICER) value was assessed and Probabilistic Sensitivity Analysis (PSA) was carried out with Monte Carlo simulation using Microsoft Excel®.Results : Epidural analgesia as anti-pain after major abdominal surgery has an Incremental Cost Effectiveness Ratio (ICER) value of IDR 20,857,416/pain free days. Probabilistic Sensitivity Analysis (PSA) produces data distribution with dominance in quadrant 3 of the CEA Plane. Conclusion : The epidural analgesia strategy for pain relief after major abdominal surgery is a cheaper strategy but with slightly lower effectiveness than intravenous opioids at RSUP Dr. Sardjito. Epidural analgesia has an ICER value of IDR 20,857,416/pain free days, has the opportunity to be an alternative choice for post-major abdominal analgetic management that is cost effective.